University students’ views about compatibility of cognitive behaviour therapy (CBT) with their personal, social and religious values (a study from Pakistan) - Naeem, Farooq (Mental health, religion & culture, 2009)
Cognitive behaviour therapy (CBT) in its current form might not be applicable in non Western cultures. Differences between Western and non Western cultures have been reported widely. Psychotherapy was developed in the West and is underpinned by many beliefs which might be specific only to the Western culture. However, in order to modify CBT, we need to understand whether the concepts associated with the CBT might cause conflicts among people who receive therapy. This study explored the beliefs of the university students in Pakistan to find out if the concepts underpinning CBT are consistent with the personal, family, socio-cultural and religious values of the university students. Discussions were held with University students in Rahim Yar Khan, Pakistan. Students were given information on various aspects of the CBT and were asked to rate their agreement with these concepts on a visual analogue scale. There was little disagreement for the principles of CBT for personal values, while some disagreement existed for religious values. This study highlights the value of assessing peoples’ beliefs about acceptability of CBT in non Western cultures. Students in Pakistan felt that the principles of CBT are consistent with their belief system in most areas. However, the value system of students might not be representative of the rest of the population.